Preface and Program - Soppela, Päivi (Rangifer, 2002)
A group of PhD students, post-doctoral scientists and senior scientists gathered together in Tromsø, August 1999 for the 1st CAES Workshop 'Reindeer 2000', in conjunction with the 10th Arctic Ungulate Conference (AUC). The purpose of the workshop was to stimulate the interdisciplinary approach and communication in studies relating to reindeer and reindeer husbandry.